Inflammatory Bowel Disease and COVID-19: How Have Patients Coped So Far?. Issue 2 (February 2022) - Schlabitz, Franziska; Teich, Niels; Riesner-Wehner, Anica; Böhm, Sebastian; Greinert, Robin; Eisenmann, Stephan; Michl, Patrick; Walldorf, Jens
Abstract : Objective: Knowledge about SARS-CoV2 and coronavirus disease 2019 (COVID-19) is growing fast. Massive changes in the health care system imposed by the COVID-19 pandemic clearly impact the overall quality of medical care. In this survey, we aim to explore experiences and concerns of patients with inflammatory bowel disease (IBD) regarding the current pandemic. Methods: A 40-item web-based questionnaire on disease-related experiences and concerns during the COVID-19 pandemic was made available to patients with IBD from 28 April 2020 to 31 July 2020. Results: An increased risk of SARS-CoV2 infection was a concern for 56.7% of the 1199 patients (aged 41.3±12.8, women 77%, Crohn's disease 58.8%, ulcerative colitis 38.5%); 61.7% feared an increased risk of severe disease course of COVID-19. Effective preventive measures in either outpatient practices or hospitals were observed by 84.7% of the patients. Appointments with an IBD specialist were canceled in 38.7%, frequently on the patients' initiative. Telecommunication visits were considered an acceptable alternative to personal visits by 71.0%. Medication was reduced or paused in 6.9% because of the pandemic. A swab (SARS-CoV2-PCR) was done in 13.2% of the patients; only 3 patients (0.25%) were tested positive. Conclusion: The COVID-19 pandemic is a major concern of patients with IBD. However, the cumulative prevalence in our cohort is low. Patients at risk should be identified and counseled individually. When required because of the local COVID-19 situation, telecommunication visits and liberal prescription policies are advisable to reduce in-person contacts, while ensuring continuous therapy and maintaining communication with patients. Abstract : Supplemental Digital Content is available in the text.